Православие в Балтии № 4 (13) - (:unkn) unknown (LU Filozofijas un socioloģijas institūts, 2016)
Žurnāla "Православие в Балтии" [Pareizticība Baltijā] Nr.4 (13) struktūru veido trīs nodaļas: zinātniskie raksti, memuāri un dokumentu publikācijas. Pirmajā nodaļā ir publicētie raksti ir veltīti ievērojamo Rīgas arhitektu - Roberta A. Pflūga, Heinriha K. Šēla un Jāņa F. Baumaņa - pareizticīgo dievnamu projektiem; Pareizticīgo baznīcai Latvijas teritorijā Pirmā kara laikā; Pareizticīgo baznīcai Polijā starpkaru laikā, kā arī divu ievērojamu Baznīcas ganu - Monreālas un Kanādas arhibīskapa Silvestra (Haruna, dzim. Daugavpilī, Latvija) un bīskapa Ioana (Bulina, dzim.Vipsu, Igaunija) - biogrāfijām. Otrajā nodaļā ir publicēts ievērojamā Latvijas arhitekta Vladimira Šervinska (1894-1975) atmiņu turpinājums. Trešajā nodaļā ir publicēti divi arhīva dokumenti - atskaite par situāciju Rīgas eparhijā (1914.) un pārskats par pareizticīgo draudzēm Peipusa ezera piekrastē (1938-1939).

The fourth issue of the “Orthodoxy in the Baltic States” consists of three sections: 1. Scientific articles; 2. Memoirs; 3. Publication of documents. Five articles are published in the first section. An article of the architectural historian, Archpriest Alexander Bertash introduces the reader to the Orthodox sacral heritage of three architects of Riga: of Robert Pflug (1832-1885), Karl Heinrich Scheel (1829-1909) and Janis-Friedrich Baumanis (1834-1891). An article by Alexander Gavrilin is devoted to the position of the Orthodox Church in the territory of Latvia during the First World War. An article of Anthony Mironovich tells about egregious facts of the closing and destruction of Orthodox churches in Poland in 1920-1930-ies. An Article of Alexei Liberovsky reminds us of the life and ministry of one of the hierarchs of the Orthodox Church in America, Archbishop of Montreal and Canada Sylvester (Haruns), born in Dvinsk (Daugavpils). Sergey Miannik tells the reader about the tragic, martyrdom earthly life of Bishop Ioann (Bulin). In the second section of the periodical, the continuation of the memoirs of architect Vladimir Shervinsky (1894-1975) is published. In the third section of the periodical, the last pre-war report on the state of the diocese of Riga for 1914 is published (publication by Alexander Gavrilin). In the same section is published a document entitled “Inspection of Orthodox churches at Chud Lake by Bishop of Narva Paul (Dmitrovskij) in 1938-1939” (publication by Tatiana Shor). All historical sources, published in the third section, are introduced into the scientific discourse for the first time.
Keywords: Православие, Латвийская Православная Церковь; Храмовая архитектура, храмостроительство в Прибалтийском крае; Архиепископ Монреальский и Канадский Сильвестр (Харун); Епископ Иоанн (Булин); Владимир Шервинский; Рижская епархия; Православные церкви Причудья; Vladimirs Šervinskis; Янис Фридрих Бауманис / Jānis Frīdrihs Baumanis; Роберт Август Пфлуг / Roberts Augusts Pflūgs; Генрих Карл Шеель / Heinrihs Kārlis Šēls; Pareizticīgo baznīcu arhitektūra; Research Subject Categories::HUMANITIES and RELIGION::Religion/Theology